Interview performance[videorecording] - Video Education Australasia (Australia : VEA, 2006)
You only get one chance to make first impression. A successful job interview can be a key moment in a person's life : preparation, presentation, coping with the experince, and follow up are all crucial factors in the process. In this program we offer helpful hints on how to cope with nerves, asking appropriate questions, body language, and ensuring the interview ends on a positive note. We also get invaluable advice from carrers consultatns and trade union representatives. Interview performance will help students understand that interviews are something we all get better at. Success is usually just around the corner.
1. Introduction -- 2. Researching for interview -- 3. Interview preparation -- 4. Presentation and body language -- 5. The interview experince -- 6. Interview follow up -- 7. Conclusion
Director, Nick Hayward ; writer, Cath Collins ; featuring, Melissa Davison, Travis Costelow ; voice, Chelsea Bruland ; camera, Leigh Tilson ; sound recordist, Rob Hornbuckle ; boom operator, Alex Gudimenko ; DVD producer, Greg Laugher ; editor, Shannon Sleeth, Nick Hayward ; online editor, Aaron Firth Donato ; audio post production, Wayne Martin ; production manager, Edwina Baden-Powell ; educational consultant, Peter Krausz ; commissioning editor, Lisa Tancredi ; producer, Ben Harding ; executive producer, Mark McAuliffe
Ann Ray, Andrew Rimmington, Michael Spiropoulus, Ray Crampton, Mary Grech, Anna Heywood, IPA, Liz Symonds
Notes also available online
Keywords: Careers; Employment interviewing; Job hunting